Audiovisual segregation in cochlear implant users. - Simon Landry; Benoit A Bacon; Jacqueline Leybaert; Jean-Pierre Gagné; François Champoux (PLoS ONE, 2012)
It has traditionally been assumed that cochlear implant users de facto perform atypically in audiovisual tasks. However, a recent study that combined an auditory task with visual distractors suggests that only those cochlear implant users that are not proficient at recognizing speech sounds might show abnormal audiovisual interactions. The present study aims at reinforcing this notion by investigating the audiovisual segregation abilities of cochlear implant users in a visual task with auditory distractors. Speechreading was assessed in two groups of cochlear implant users (proficient and non-proficient at sound recognition), as well as in normal controls. A visual speech recognition task (i.e. speechreading) was administered either in silence or in combination with three types of auditory distractors: i) noise ii) reverse speech sound and iii) non-altered speech sound. Cochlear implant users proficient at speech recognition performed like normal controls in all conditions, whereas non-proficient users showed significantly different audiovisual segregation patterns in both speech conditions. These results confirm that normal-like audiovisual segregation is possible in highly skilled cochlear implant users and, consequently, that proficient and non-proficient CI users cannot be lumped into a single group. This important feature must be taken into account in further studies of audiovisual interactions in cochlear implant users.